Klebsiella pneumoniae IDENTIFICATION OF PRODUCING EXTENDED SPECTRUM BETA LACTAMASE (ESBL) AND RESISTANCE PATTERN OF ANTIBIOTICS IN ULIN GENERAL HOSPITAL BANJARMASIN - Ayudiah Puspita Mayasari (Fakultas Kedokteran Universitas Lambung Mangkurat, 2017)
Abstract: Klebsiella pneumoniae(K. pneumoniae) can synthesize beta lactamase enzymes that have the ability to open lactam beta rings and cause resistance to antibiotics such as amoxicillin, third generation cephalosporins namely cefotaxim, ceftazidim, ceftriaxone and monobactam groups such as aztreonam. Extended spectrum beta lactamase (ESBL) is a plasmid enzyme that mediates the occurrence of hydrolysis and inactivation of beta lactam antibiotics. Infections caused by ESBL-producing bacteria become a serious problem for hospitals worldwide. ESBL isolate susceptibility tests against antibiotics are required to provide a sensitivity pattern that can be used as a reference in more rational antibiotic selection. This study was conducted to describe the prevalence of ESBL group K. pneumoniae and antibiotic resistance pattern at Ulin General Hospital Banjarmasin. The method of this research used secondary data material in the form of reporting document of antibiotic sensitivity test result that isolation and identification using VITEK 2, and then be analyzed using Microsoft Excel. The culture examination toward 50 patients in the Dahlia ward, Ulin General Hospital Banjarmasin was taken from January until May 2017, with the results arefrom 24 data Staphylococius aureus (S.aureus) isolate, more than half of it are ESBL group (54.16%). The results of sensitivity test of K.Pneumoniae of ESBLpositive to antibiotic group were found to be antibiotics that still have> 90% sensitive were meropenem (100%), amikacin (100%), tigecycline (92,85%), ertapenem (92,86%). The antibiotics with resistance> 50% was found in ampicillin antibiotics (100%), ceftriaxone (78.5%), ceftazidime (64.28%), cefepime (57.14%) and aztreonam (71.4%). As for ESBL negative results obtained sensitive> 90% for all antibiotics except ampicillin, ampicillin / sulbactam, and nitrofurantoin. Meropenem (100%), amikacin (100%), tigecycline (92.85%), ertapenem (92.86%) are antibiotic choices that are still sensitive to ESBL infection Keywords: antibiotic resistance, ESBL pattern, Vitek 2